2018
DOI: 10.1051/epjconf/201817511024
|View full text |Cite
|
Sign up to set email alerts
|

Topological Susceptibility under Gradient Flow

Abstract: Abstract. We study the impact of the Gradient Flow on the topology in various models of lattice field theory. The topological susceptibility χ t is measured directly, and by the slab method, which is based on the topological content of sub-volumes ("slabs") and estimates χ t even when the system remains trapped in a fixed topological sector. The results obtained by both methods are essentially consistent, but the impact of the Gradient Flow on the characteristic quantity of the slab method seems to be differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Spin diffusion along the t-channel 23 can be viewed as being mediated by reggeon exchange (corresponding to the η 0 ) in the isosinglet sector. At large x B , g 1 can be computed using lattice QCD methods [24][25][26][27][28][29]68]. However at small x B , particularly in Regge asymptotics, lattice computations are challenging due to the difficulties posed by i) computing higher moments of local operators, ii) boosting the proton to high energies on the lattice [69].…”
Section: Axion-like Action At Small Xb: Gluon Saturation and Sphalero...mentioning
confidence: 99%
See 2 more Smart Citations
“…Spin diffusion along the t-channel 23 can be viewed as being mediated by reggeon exchange (corresponding to the η 0 ) in the isosinglet sector. At large x B , g 1 can be computed using lattice QCD methods [24][25][26][27][28][29]68]. However at small x B , particularly in Regge asymptotics, lattice computations are challenging due to the difficulties posed by i) computing higher moments of local operators, ii) boosting the proton to high energies on the lattice [69].…”
Section: Axion-like Action At Small Xb: Gluon Saturation and Sphalero...mentioning
confidence: 99%
“…In the Bjorken limit, as we will discuss briefly, the formalism of Shore and Veneziano goes through for g 1 (x B , Q 2 ), precisely as for its first moment Σ(Q 2 ). The corresponding matrix element can be computed on the lattice similarly to prior lattice computations [24][25][26][27]. For discussions of how to extract Σ(Q 2 ) directly from the slope (with t) of the topological susceptibility, see [28]; a recent review of lattice extractions of the topological susceptibility can be found in [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation